PERAN SUPERVISOR DALAM MENGEMBANGKAN SUMBER DAYA MANUSIA DIRESTAURANT SECTION HOTEL ISHINE PEKANBARU - Suci Chamiko Putri; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Human resource development is a business process undertaken to develop the knowledge, skills and abilities of employees. The importance of developing the capabilities of existing employees is very influential in achieving company goals. The role of supervisors is important in developing human resources because supervisors as leaders for their employees are very influential in the implementation of human resource development. This study aims to (1) to determine the role of supervisor in developing human resources in the restaurant section of iShine Hotel Pekanbaru (2) to find out what obstacles for supervisors play a role in developing human resources in restaurant section iShine Hotel Pekanbaru. This research design using qualitative method with descriptive approach, which the researchers will take data from informants who know clearly about the role of supervisor in developing human resources in restaurant section Hotel iShine Pekanbaru.The results showed that the role of supervisors in the restaurant section of iShine Hotel Pekanbaru is instrumental in improving the ability of subordinates, gradual development and handle the decline in the performance of subordinates. Supervisors obstacles in developing human resources in restaurant section iShine Hotel Pekanbaru in general is the lack of budget in training (training), lack of subordinate motivation, and lack of completeness of equipment in the restaurant section.Keywords: Role Supervisor, Human Resources, Human Resource Development, Hotel iShine Pekanbaru